Comparing the effect of adding intrathecal morphine versus dexmedetomidine as adjuvant to bupivacaine in spinal anaesthesia for lower limb orthopaedic surgery - Noordin, Mohammad Faiz Mohammad (2018)
Background: We studied the effect of adding intrathecal morphine versus dexmedetomidine as adjuvant to bupivacaine in lower limb orthopaedic surgery. The onset and the duration of spinal anaesthesia were assessed using clinical examination. Methods: Thirty-six patients, aged 18-60 year old, classified under ASA 1-2, who underwent elective lower limbs orthopaedic surgery under spinal anaesthesia, were randomised into two groups: group morphine (n=18) and group dexmedetomidine (n=18). Spinal anaesthesia was performed and in group morphine 2.5 ml of 0.5% hyperbaric bupivacaine and 0.2 mg morphine in 0.5 ml of normal saline were administered intrathecally. In group dexmedetomidine, 2.5 ml of 0.5% hyperbaric bupivacaine and 5 μg dexmedetomidine in 0.5 ml normal saline. Measurement of sensory block according to dermatome level, Bromage scale for motor assessment and post operative pain score were recorded for statistical analysis. Data were tested by independent t-test and repeated measure ANOVA analysis. Results: There was no significant difference with regard to the duration to reach T10 between morphine and dexmedetomidine (p>0.05). There was a significant difference with regard to time (mean) to reach Bromage 3 between morphine and dexmedetomidine (p<0.05). The time [mean (SD)] to reach Bromage 3 for morphine was 4.56 (0.78) minutes and for dexmedetomidine was 3.83 (0.79) minutes indicating that the time to reach Bromage 3 was lower in dexmedetomidine. There was a significant difference with regard to time taken to reach Bromage 0 between morphine and dexmedetomidine (p<0.05). The [mean (SD)] to reach Bromage 0 for morphine was 134.44 (20.64) minutes and for dexmedetomidine was 276.67(54.02) minutes indicating that the time to reach Bromage 0 was higher in dexmedetomidine. For time-treatment interaction results in repeated measure ANOVA analysis, we found that there was a significant difference between pain score of groups based on time (F= 2.54, p= 0.031). The mean pain score was higher for those who took dexmedetomidine compared to morphine. Conclusions: Intrathecal dexmedetomidine significantly cause prolonged in sensory and motor block in comparison with intrathecal morphine. However for post-operative pain control, intrathecal morphine gave better pain control post-operatively